Extra-Linguistic Factors and Tendencies of Activation of Military Vocabulary in Ukrainian Mass Media - Navalna, Maryna; Kostusiak,Nataliia; Levchenko, Tetiana; Oleksenko, Volodymyr; Shyts, Andriy; Popkova, Oksana (My University, 2022)
The article characterizes the most used tokens in the texts of modern Ukrainian mass media, reveals new and with new variants of meanings lexical units, traces the expansion of the scope of military tokens not only in specialized media, but also in texts on socio-political, economic, and other spheres of activities; the functional and stylistic role of this vocabulary in the language of mass media is determined and its negative assessment in journalistic materials is emphasized. To study military vocabulary in the Ukrainian mass media of the early 21st century, we used descriptive method as the main method of observation. At different stages of the research, the method of functional analysis was applied, which allowed determining the stylistic load of lexical units. It was found that due to a number of extralinguistic factors of socio-political orientation (annexation of Crimea, Russian-Ukrainian conflict in eastern Ukraine), the modern Ukrainian language was supplemented by new tokens, and well-known nominations of this meaningful variety for persons, actions, processes, states, etc. were updated, which is reflected in the media of the second and early third decades of the 21st century. The tokens for naming individuals, groups and territories have become the most popular. Under the influence of extralingual factors, many new abbreviations have emerged. Often the analyzed tokens have a negative color, contrast with neutral vocabulary and at the same time serve as a means of attracting the reader's attention.
Keywords: abbreviation; extralingual factors; military vocabulary; negative assessment; scope; stylistic role